Factors Analyses Associated with Growth and Children Development Under Five Years Old in the Area of Cilacap Coastal - Ridlo, Rizky Fachrian; Rusana, Rusana; Subandi, Ahmad; Ariani, Ida (Prosiding University Research Colloquium, 2022)
Children under five years old is a golden period of physical, intellectual, mental and emotional growth of children. Several factors that influence growth and development are internal and external factors. The purpose of this study was to determine the factors related to the growth and development of children under five years old in the area of Cilacap Coastal. The design used is an analytical survey with a cross sectional design. The sample size was 110 parents and children under five years old with cluster random sampling technique. Data analysis using chi square test. The results showed that there was a relationship between nutritional status, stimulation, parental income, and parental education with growth according to body weight (pv = 0.000; pv = 0.000; pv = 0.000 and 0.001). There was a relationship between nutritional status, stimulation and parental income with growth according to TB/U (pv=0.000; pv=0.003; pv=0.006). There was a significant relationship between nutritional status, stimulation, income and parental education with development (pv=0.000; pv=0.001; pv=0.000; pv=0.000). There was no relationship between parental education and the growth of TB/U (pv=0.089) and parenting with the growth of BB/U, TB/U and the development of children under five years old in the area of Cilacap Coastal (pv= 0.259; pv= 0.142; pv= 0.941).